Synthesis, Characterization and Antimicrobial Activity of N-2-(4-Chlorophenyl)acetyl Derivatives of (S)-Amino Acids - Venkateshappa, G.; Kumar, P. Raghavendra; Krishna (Asian Journal of Chemistry, 2019)
This paper reports the synthesis, characterization and antibacterial activity of N-2-(4-chlorophenyl)acetyl derivatives of various (S)-amino acids such as (S)-alanine, (S)-phenylalanine, (S)-leucine, (S)-methionine, (S)-proline and (S)-tryptophane. These compounds have been successfully synthesized and their structures were confirmed by 1H NMR and 13C NMR and FT-IR spectroscopy. The antimicrobial activity of these six (S)-amino acids derivatives have been evaluated by the agar well diffusion method against pathogens both Gram-positive (S. aureus) and Gram-negative (K. aerogenes, E. coli and P. desmolyticumas) bacteria and fungi (A. flavus and C. albicans). All these compounds have shown mild to moderate antimicrobial activity.